Collision of waterpipe and cigarette smoking epidemics among youth in Arab countries. (2nd September 2016) - Kheirallah, Khalid A.; Veeranki, Sreenivas P.; Alzyoud, Sukaina; Alzoubi, Abdallah; Walker, Leah; Khader, Yousef; Mzayek, Fawaz; Pbert, Lori; Ward, Kenneth D.
Abstract: Background : Waterpipe tobacco smoking (WTS) emerges as a new component of the global tobacco epidemic. Adolescents smoking waterpipe are susceptible to cigarette smoking, but limited research has characterized dual (cigarette plus waterpipe) users. The study objective is to determine the prevalence estimates of dual users to understand how "collision" of the two epidemics is evolving in the Arab countries. Methods : Data ( n = 31, 359; N = 6, 109, 572) were obtained from nationally representative Global Youth Tobacco Surveys (GYTSs) from 17 Arab countries. Current tobacco use was categorized into four groups—cigarette smoking only, WTS only, dual use, and never use. Weighted age-, sex-, and country-specific prevalence estimates along with 95% confidence intervals were reported. Results : Overall 3.0%, 6.1%, and 3.8% of youth were cigarette smokers only, WTS only, and dual users. Boys reported high prevalence estimates of cigarette smoking only (5.1% vs 1.1%), WTS only (7.4% vs 4.6%), and dual use (3.7% vs 2.1%) than girls. Dual-use estimates ranged from 0.7% in Oman to 15.0% in West Bank and WTS only ranged from 0.9% in Oman to 6.6% in United Arab Emirates. Conclusion : Dual use and WTS is well established among Arab youth and represents a new dimension to the global tobacco epidemic that may not respond to traditional tobacco control interventions.